Drafting copyright exceptions : from the law in books to the law in action / Emily Hudson. - Hudson, Emily (Cambridge intellectual property and information law ;, 2020)
How should copyright exceptions be drafted? This is a question of ongoing concern in scholarly and law reform debates. In Drafting Copyright Exceptions, Emily Hudson assesses drafting options using insights from the standards and rules literature, and case studies from cultural institutions in Australia, Canada, the UK and the US. Drawing on thousands of hours of fieldwork conducted over fourteen years, the book describes how staff engage with and interpret the law. Whilst some practices are guided strongly by copyright doctrine, others are influenced by the factors such as ethical views, risk assessment, and prosaic matters related to collection management. This work should be read by anyone interested in a detailed account of interpretative practices related to the drafting of copyright exceptions, but it also speaks to broader debates about the relationship between the 'law in books' and the 'law in action'.